رەنگدانەوەى هونەرەکانى ڕۆژنامەنووسیى و رۆشنبیریى کوردیى پەنجاکانى شارى هەولێر لە گۆڤارىى(هەتاو) دا - بەکر, م. هیمداد حسێن (Sulaimani Journal for Humanities, 2025)
In his Study, the Researcher Tries to give a true picture of the intellectual and cultural life in the fifties and role of the Geo Mukuryani in preparing the new generation concerning the litrary life at that time .Along with that, the researcher discusses the press arts such as the art of essay ,news, columns ...etc